The price and affordability of essential medicines, progress and regional distribution in China: a systematic review - Liu, Zheng; Zou, Kun; Liu, Dan; Zhang, Miao; Shi, Yuqing; Chen, Zhe; Lang, Bingchen; Cheng, Xiao; Li, Hailong; Zeng, Linan; Tang, Yong; Zhao, Shaoyang; et al. (Frontiers in Pharmacology, 2023)
Background: Essential medicine is a vital component to assure universal access to quality healthcare. However, the trend of affordability to essential medicines in China and its regional differences were not yet fully understood. This study aimed to systematically evaluate the price and affordability of essential medicines, their progress, and regional distribution in China in the last decades. Methods: We searched seven databases and three websites for potentially eligible studies from inception until March 2022. Studies on the price and affordability of essential medicines investigated in China were included. Median and interquartile range (IQR) was used to describe the price and affordability of essential medicines, and compared in three periods, before 2009, from 2009 to 2014, and from 2015 to 2019. Subgroup analysis was performed to examine the price and affordability by regions, health facilities, and ATC categories of medicines. The study was registered with PROSPERO (CRD42022310173). Results: A total of 65 studies including 11639 health facilities investigated between 2006 and 2019 were included in this review. Median price ratios (MPR) and affordability of essential medicines were reported in 44 studies and 50 studies, respectively. The median MPRs of essential medicines in China was 1.59 (IQR: 5.39), with a tendency to rise first and then fall from 2006 to 2019. And the median affordability was equal to 0.88 (IQR: 2.58) days’ wage of the lowest paid unskilled government worker, but steadily rose from 2006 to 2019. Subgroup analysis showed that the affordability in the western region (1.40, IQR: 2.88), urban area (0.95, IQR: 2.80), private sector (0.90, IQR: 2.30), of OB drugs (2.90, IQR: 6.68), and antineoplastic and immunomodulating agents (5.68, IQR: 56.47) were worse than their counterparts. Conclusion: The prices of essential medicine were higher than international level, the overall affordability of essential medicines in China is acceptable but poor in the western region, for OB drugs and anti-cancer medicines. Further national essential medicine policies are needed to reduce regional disparities and improve the affordability of expensive drugs.